Labeling farmed seafood: A review. Issue 1 (2nd January 2018) - Alfnes, Frode; Chen, Xianwen; Rickertsen, Kyrre
ABSTRACT: Food labels help consumers choose products in line with their food attitudes and preferences. As the market for farmed seafood grows, it is important for producers to meet consumer demand for credence characteristics like safety, nutrition, origin, and sustainability. Consumer preferences for credence characteristics are heterogeneous, and stakeholders in the farmed seafood industry can look to both agriculture and marine labels when they seek ways of positioning their products. In this article, we conduct a review of consumer studies related to mandatory and voluntary labels used for farmed seafood. In most developed countries, mandatory seafood labels include information about species, farmed or wild, and area of origin. Voluntary labels include information regarding sustainability, organic production, animal welfare, traceability, and safety. We point to emerging research topics and possibilities. Challenges related to the labeling of farmed seafood are also discussed.